2013
DOI: 10.1002/smll.201202840
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Yolk–Shell Materials with Single, Binary, Ternary, Quaternary, and Quinary Systems

Abstract: A facile, one-pot method of systematically synthesizing yolk-shell materials with complex compositions is proposed. The spray pyrolysis process for obtaining yolk-shell materials is advantageous because it is highly efficient, allows high throughput, comprises a single-step reaction, and is a continuous process that yields homogeneous composition and enables facile control of the mean size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 40 publications
(62 reference statements)
0
42
0
Order By: Relevance
“…The spray pyrolysis system applied in this study is shown in Figure S8. 22,23 The reactor temperature during the spray pyrolysis process was fixed at 800 °C. …”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
“…The spray pyrolysis system applied in this study is shown in Figure S8. 22,23 The reactor temperature during the spray pyrolysis process was fixed at 800 °C. …”
Section: Synthesis Of Catalystsmentioning
confidence: 99%
“…Combustion, contraction, and recombustion processes occurred in a step-by-step manner as the CuO-Fe 2 O 3 -carbon composite intermediate progressed through the reactor, finally producing yolk-shell-structured CuO-Fe 2 O 3 powders irrespective of compositions. [22][23][24] Heat evolved from the combustion of carbon resulted in the crystalline CuO-Fe 2 O 3 powders with uniform composition. The compositions of the yolkshell CuO-Fe 2 O 3 powders were analyzed by inductively coupled plasma-optical emission spectrometry (ICP-OES, Table S1, the Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27] Recently, a simple spray pyrolysis process was successfully applied to the preparation of yolk-shell-structured powders. [22][23][24] Using this one-pot spray pyrolysis process, materials with single, binary, ternary, quaternary, and quinary yolkshell structures were successfully produced under the same preparation conditions. [24] The electrochemical properties of the yolk-shell-structured materials with single and binary metal oxides prepared by spray pyrolysis were mainly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, spray pyrolysis, which is one of the scalable gas‐phase reaction methods, has been successfully applied to the large‐scale production of yolk–shell‐structured materials of various compositions. In spray pyrolysis, a repeated combustion and contraction process of a metal oxide‐carbon composite, which forms as an intermediate product, leads to the formation of carbon‐free metal oxide microspheres with a yolk–shell structure . The multishelled powders with carbon interlayer have been prepared by multistep liquid solution processes as intermediate product to synthesize the metal oxide yolk–shell powders .…”
Section: Introductionmentioning
confidence: 99%